2011
DOI: 10.1111/j.2044-3862.2011.00035.x
|View full text |Cite
|
Sign up to set email alerts
|

Presenting signs of foot abscessation - A practice based survey of 150 cases

Abstract: : Foot abscesses are one of the commonest causes of lameness encountered in equine practice. This practice based survey of 150 cases demonstrates that being unshod is a major risk factor and that the degree of reported lameness is extremely variable. It also demonstrates that the white line was the usual point of entry (147/150 cases). Whilst the fore feet are more often affected than the hind feet there was no difference in the rate of occurrence between the medial and lateral sides. Application of a shoe has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 3 publications
3
1
0
Order By: Relevance
“…This is in agreement with a previous study2 showing that the right forefoot was most commonly affected. The reasons for this remain unclear.…”
supporting
confidence: 94%
See 2 more Smart Citations
“…This is in agreement with a previous study2 showing that the right forefoot was most commonly affected. The reasons for this remain unclear.…”
supporting
confidence: 94%
“…The study by Cole and colleagues 1 showed that subsolar abscesses are more common in forelimbs, with the right forelimb being the most commonly affected. This is in agreement with a previous study 2 showing that the right forefoot was most commonly affected. The reasons for this remain unclear.…”
supporting
confidence: 94%
See 1 more Smart Citation
“…2c) lesion was recorded in hind foot of 2 male horses only. However, Stephenson (2011) stated that the fore feet were more often affected than the hind feet and the white line was the usual point of entry in unshod horses. Moreover, radiography was the most commonly used diagnostic technique for solar abscess that reveals a smoothly marginated, radiolucent defect in the solar margin of the distal phalanx (Redding and Grady 2012).…”
Section: Resultsmentioning
confidence: 99%